Adjunctive treatment of myxopapillary ependymoma running head: Myxopapillary ependymoma - Amin Jahanbakhshi; Masoumeh Najafi; Fatemeh Jafari; Mahsa Moshtaghian; Marzieh Gomar; Mousareza Anbarlouei; Soheil Naderi (Frontiers Media S.A., 2021)
Myxopapillary ependymoma are rare tumors and optimal therapeutic strategy is remained controversial. The main treatments for myxopapillary ependymoma tumors include surgery and radiotherapy. Hence, the present study aimed to review adjuvant treatment of myxopapillary ependymoma, focusing on spinal myxopapillary ependymoma. The information sources of all articles were the English authoritative databases including PubMed, Web of science, Scopus, Science direct and Google scholar. In this review study, the keywords including adjuvant, treatment, myxopapillary and ependymoma were selected from MeSH medical library. Related articles were published from 2000 to 2020. Given radiation tolerance in the spinal cord is 10-15% lower than that of the brain, it also should be noted that with increased dose and scope of therapeutic field, the corresponding risks are increased, as well. Also, chemotherapy has never been used as the primary treatment approach. Radiotherapy's value is considered while involving with sensitive areas where chemotherapy is also recommended. Gross total resection is the preferred primary treatment. But the role of adjuvant radiotherapy is debated in different tumor and patient scenarios and no standard treatment strategy had been defined yet. The bottom line is that as long as cellular and molecular methods or gene therapy can be used in the treatment of myxopapillary ependymoma, all the studies confirm that the best treatment method is still wide surgical resection as much as possible.